2019
DOI: 10.1029/2018jc014529
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐optical Properties of Surface Waters in the Atlantic Water Inflow Region off Spitsbergen (Arctic Ocean)

Abstract: Bio‐optical properties of surface waters were characterized off western and northern Spitsbergen in the summers of 2013, 2014, and 2015. We observed statistically significant year‐to‐year differences in spatial distribution of spectral absorption (a(λ)) and beam attenuation (c(λ)). Highest a(λ) and c(λ) were located in the frontal zone between water masses and co‐varied strongly with chlorophyll a fluorescence. Phytoplankton pigments dominated the absorption budget at 443 nm (50%). The contribution of chromoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 92 publications
4
31
1
Order By: Relevance
“…Sample-based values of aphy(440) and aNAP(440) (Figure 8, middle and bottom) and their distribution with depth were in similar range as reported in WSC waters by (Kowalczuk et al, 2017(Kowalczuk et al, , 2019, further pointing to the presence of AW dominated waters. Although not targeting the subsurface chl-a maxima at time of sampling (since in situ data was not available to guide the water sampling), the sample-based phytoplankton absorption at 440 nm (Figure 8, middle) indicates increased absorption by phytoplankton in the subsurface, and at deeper depth in the southern fjord compared to the central part of the fjord.…”
Section: Characteristics Of Particulate Mattersupporting
confidence: 74%
See 2 more Smart Citations
“…Sample-based values of aphy(440) and aNAP(440) (Figure 8, middle and bottom) and their distribution with depth were in similar range as reported in WSC waters by (Kowalczuk et al, 2017(Kowalczuk et al, , 2019, further pointing to the presence of AW dominated waters. Although not targeting the subsurface chl-a maxima at time of sampling (since in situ data was not available to guide the water sampling), the sample-based phytoplankton absorption at 440 nm (Figure 8, middle) indicates increased absorption by phytoplankton in the subsurface, and at deeper depth in the southern fjord compared to the central part of the fjord.…”
Section: Characteristics Of Particulate Mattersupporting
confidence: 74%
“…As it could also be assessed qualitatively from Figure 10, this also highlights the strong dependence of the absorption budget to the wavelength of the radiation, the CDOM contribution dramatically decreasing with increasing wavelength. The relative CDOM contribution was thus higher than what has been found in the Atlantic water in the West Spitsbergen Current (WSC) with average CDOM contribution of 42% at 412nm (Kowalczuk et al, 2019), as well as in AW north of Svalbard with CDOM contribution of 43% at 443nm (Kowalczuk et al, 2017)…”
Section: Relative Contribution Of the Optically Active Constituentsmentioning
confidence: 73%
See 1 more Smart Citation
“…CDOM represents an essential constituent affecting ocean color. Thus, in the Arctic Ocean, the contribution of a CDOM (443) to the total non-water absorption can reach~50% [73]. It was shown that systematic differences in chlorophyll retrievals resulting from different ocean color models are related to each model's ability to account for the absorption of light by CDOM [14].…”
Section: Cdom Absorption At 350 Nm and 440 Nmmentioning
confidence: 99%
“…To better understand these dependencies, future protist studies should relate to mesoscale phenomena, be supplemented by at least mesozooplankton data and water chemistry, and have an equivalent in springtime. Because recent satellite-derived and bio-optical in situ surveys suggested rapid expansion of temperate phototrophic protists (mainly coccolithophores) in the Arctic (e.g., Dylmer et al, 2015;Neukermans et al, 2018;Kowalczuk et al, 2019), it would also be reasonable to confirm these suppositions by microscopic studies. Our research does not support these findings.…”
Section: Recommendations For Future Studiesmentioning
confidence: 99%